The Effect of CEO education on the financial performance of firms listed in the Nairobi Securities Exchange: the moderating role of CEO experience - Wachira, J. W. (Strathmore University, 2025)
Companies often ask how to boost their financial performance. Extensive research highlights numerous factors influencing financial performance. One key factor is the education level of the executive directors. This study’s main objective was to examine the effect of chief executive officer’s (CEO) education on the financial performance of firms listed at the Nairobi Securities Exchange (NSE), with CEO experience as the moderating variable. More specifically, the study sought to examine the effect of the level of education on firm financial performance, the type of education on firm financial performance and the location of the educational institution on firm financial performance. To achieve these objectives, an explanatory research design was adopted in which both primary and secondary data was obtained from a population of 67 firms listed in the Exchange. Since the population was small, a census sampling methodology was applied and all the firms listed were included in the sample. A document review method was used to collect secondary data on the study variables. From the data analysis, there was a statistically significant positive correlation between financial performance as measured by return on assets and the level of education, suggesting that CEOs with higher levels of education are associated with better financial performance. The regression analysis further showed that that the level of education had a significant positive effect on financial performance, indicating that for every unit increase in the level of CEO education, financial performance increased. The analysis further showed a significant but weak negative correlation between the type of education and financial performance. This suggests that where CEO’s education was more business oriented, financial performance would slightly decline. Lastly, the correlation and regression analysis showed that the location of the educational institution had a positive but insignificant correlation with financial performance. The location of the educational institution had no significant effect on performance as indicated by the weak regression coefficient. Introducing CEO experience as a moderating variable increased the R-squared value. This indicated that CEO education and experience together explained better the variance in financial performance. The interaction between CEO experience and level of education and type of education showed a significant moderating effect, suggesting that CEO experience enhances the impact of these educational dimensions on financial performance. However, the interaction between the location of the educational institution and financial performance was insignificant. The study therefore concluded that level of CEO education has a positive effect on financial performance. However, the type of education and location of educational institution have no effect on financial performance of NSE listed firms. The study therefore recommends that regulatory bodies such as the Capital Markets Authority (CMA) and NSE should encourage firms to prioritize hiring CEOs with higher levels of education, such as postgraduate qualifications. Firms should incorporate advanced educational qualifications as part of their executive recruitment criteria. Firms should prioritize candidates with MBA, master's, or PhD degrees as part of their leadership pipeline development strategies. This can improve overall firm financial performance and competitiveness.
Full - text thesis